Academic, research and diffusion activities of the Scientific Societies of Dental Students in Peru - Castro-Rodríguez, Yuri (2022)
Objective. Describe the activities and characteristics of the Peruvian Scientific Societies of Dental Students (SCEO). Methods. Descriptive and prospective study that had as a study population the total of existing Peruvian SCEO until October 2021. A collection sheet was prepared about the sociodemographic and training characteristics (year of foundation, number of members, activity), also on the academic, research and dissemination activities through social networks. The activities disseminated on institutional social networks were recorded and the leaders of each SCEO were surveyed to expand the information obtained and request the scientific production records of each SCEO, which was corroborated through searches in Scopus, WoS, SciELO, etc. Results. Ten SCEO were identified; nine had less than two years of experience and six reported that they were still active in their functions. The development of methodology, biostatistics and thesis seminars were the academic training activities found as well as the development of a Critical Reading Club. Eight SCEOs shared their academic activities through social networks as well as audiovisuals (infographics, posters, academic videos, etc). Five SCEOs indicated submitting at least one scientific publication; one of them presented 42 published articles, of which 19 (45%) were found in the Scopus database. Conclusions. SCEOs are in the early stages of their formation. Its main academic and investigative activities focus on the formation of investigative competencies of its members, likewise, these activities are disseminated through its social networks.